2020
DOI: 10.1080/23312025.2020.1809820
|View full text |Cite
|
Sign up to set email alerts
|

Studying the morphological diversity of Bunium paucifolium and some Elwendia species (Apiaceae)

Abstract: The genus Bunium L. (Apiaceae) has about 50 species in the world, distributed in Asia, Europe and North Africa. Recently, Bunium has been divided into two separate genera Elwendia and Bunium. Kerman province is the largest province in Iran and has a wide distribution of these genera especially E. persica, as the most important medicinal and spice species. There are a few published studies on the morphology of these genera, especially on flower and fruit morphology. 20 morphological traits were studied to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Plant growth‐related parameters, secondary metabolites biosynthesis, and their biological properties are influenced by environmental stresses, growth stimulants, and geographical and genetic factors (Sampaio et al, 2016 ; Ghorbanpour et al, 2016 ; Selmar et al, 2017 ; Meftahizadeh et al, 2019 ; Pourhosseini et al, 2020 ; Mohammadi et al, 2021 ; Mirheidari et al, 2022 ). Previous studies have shown the importance of certain morphological and biochemical traits regarding the productivity of plants in the Apiaceae family (Ninou et al, 2017 ; Adelifar et al, 2020 ; Jorkesh et al, 2020 ;). However, little is known about the phenotypic diversity and biochemical variation of E. caucasicum in different natural habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Plant growth‐related parameters, secondary metabolites biosynthesis, and their biological properties are influenced by environmental stresses, growth stimulants, and geographical and genetic factors (Sampaio et al, 2016 ; Ghorbanpour et al, 2016 ; Selmar et al, 2017 ; Meftahizadeh et al, 2019 ; Pourhosseini et al, 2020 ; Mohammadi et al, 2021 ; Mirheidari et al, 2022 ). Previous studies have shown the importance of certain morphological and biochemical traits regarding the productivity of plants in the Apiaceae family (Ninou et al, 2017 ; Adelifar et al, 2020 ; Jorkesh et al, 2020 ;). However, little is known about the phenotypic diversity and biochemical variation of E. caucasicum in different natural habitats.…”
Section: Introductionmentioning
confidence: 99%